Disability: leaning away from the curve. Issue 11 (23rd March 2022) - Jesudason, Edwin
Abstract : This response to Evans et al encourages broader consideration of what constitutes disability, extending beyond a protagonist's capabilities toward society's fuller chorus. Three avenues are submitted to encourage this. First, Engel's biopsychosocial paradigm of health can be helpfully applied to the question of identity in general, and disability in particular. Second, the philosophy of language (and of naming) gives useful insight into the pitfalls of trying to define disability via descriptions of capability. Third, Kennedy's critique 'Unmasking Medicine' offers a sociopolitical view that builds on Foucault and Illich allowing us to recognise that it matters who judges who, as disabled, and on what grounds. Alongside this, I suggest alternative views first, on the authors' liberal use of bell curves in the depiction of disability and second, on their terminology of capacity spaces.